A commercial Roundup® formulation induced male germ cell apoptosis by promoting the expression of XAF1 in adult mice. (15th October 2018) - Jiang, Xiao; Zhang, Ning; Yin, Li; Zhang, Wen-long; Han, Fei; Liu, Wen-bin; Chen, Hong-qiang; Cao, Jia; Liu, Jin-yi
Highlights: Excessive apoptosis of male germ cell occurs after Roundup® exposure. Over-expression of XAF1 triggers germ cell apoptosis following Roundup® exposure. Roundup® exposure has potential toxicity on male reproductive health in mammals. Abstract: Roundup® is extensively used for weed control worldwide. Residues of this compound may lead to side effects of the male reproductive system. However, the toxic effects and mechanisms of Roundup® of male germ cells remain unclear. We aimed to investigate the apoptosis-inducing effects of Roundup® on mouse male germ cells and explore the role of a novel tumor suppressor XAF1 (X-linked inhibitor of apoptosis-associated factor 1) involved in this process. We demonstrated that Roundup® can impair spermatogenesis, decrease sperm motility and concentration, and increase the sperm deformity rate in mice. In addition, excessive apoptosis of germ cells accompanied by the overexpression of XAF1 occurred after Roundup® exposure both in vitro and in vivo. Furthermore, the low expression of XIAP (X-linked inhibitor of apoptosis) induced by Roundup® was inversely correlated with XAF1. Moreover, the knockdown of XAF1 attenuated germ cell apoptosis, improved XIAP expression and inhibited the activation of its downstream target proteins, caspase-3 and PARP, after Roundup® exposure. Taken together, our data indicated that XAF1 plays an important role in Roundup®-induced male germ cell apoptosis. The present study suggested that Roundup® exposure has potential negative implications on male reproductive health in mammals.